Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Phosphorus Zoning in Olivines: A critical tool for tracking magma ascent and storage in the martian crust - Arka P. Chatterjee; Julien Allaz; Christian Huber; Luiz F.G. Morales; Amanda Ostwald; Olivier Bachmann (Geochimica et Cosmochimica Acta, 2026)

CONFLUX: A standardized framework to calculate reactor antineutrino flux - Xianyi Zhang; Anosh Irani; Michael P. Mendenhall; Nathan Rybicki; Leendert Hayen; Nathaniel Bowden; Patrick Huber; Bryce Littlejohn; Sandra Bogetic (Computer Physics Communications, 2025)

Erratum to “Screening the release of chemicals and microplastic particles from diverse plastic consumer products into water under accelerated UV weathering conditions” [J Hazard Mater 477 (2024) 135256] - Frank Menger; Mara Römerscheid; Stefan Lips; Ole Klein; Deedar Nabi; Jürgen Gandrass; Hanna Joerss; Katrin Wendt-Potthoff; Daria Bedulina; Tristan Zimmermann; Mechthild Schmitt-Jansen; Carolin Huber; et al. (Journal of Hazardous Materials, 2025)

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Corrigendum to “Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies” [Sci. Total Environ. Volume 951 (2024) 175727] - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Screening the release of chemicals and microplastic particles from diverse plastic consumer products into water under accelerated UV weathering conditions - Frank Menger; Mara Römerscheid; Stefan Lips; Ole Klein; Deedar Nabi; Jürgen Gandrass; Hanna Joerss; Katrin Wendt-Potthoff; Daria Bedulina; Tristan Zimmermann; Mechthild Schmitt-Jansen; Carolin Huber; et al. (Journal of Hazardous Materials, 2024)

Late summer northwestward Amazon plume pathway under the action of the North Brazil Current rings - L. Olivier; G. Reverdin; J. Boutin; R. Laxenaire; D. Iudicone; S. Pesant; Paulo H.R. Calil; J. Horstmann; D. Couet; J.M. Erta; P. Huber; H. Sarmento; et al. (Remote Sensing of Environment, 2024)

Globally‐distributed microbial eukaryotes exhibit endemism at deep‐sea hydrothermal vents - Sarah K. Hu; Amy R. Smith; Rika E. Anderson; Sean P. Sylva; Michaela Setzer; Maria Steadmon; Kiana L. Frank; Eric W. Chan; Darlene S. S. Lim; Christopher R. German; John A. Breier; Susan Q. Lang; et al. (Molecular Ecology, 2023)
Single‐celled microbial eukaryotes inhabit deep‐sea hydrothermal vent environments and play critical ecological roles in the vent‐associated microbial food web. 18S rRNA amplicon sequencing of diffuse venting fluids from four geographically‐ and geochemically‐distinct hydrothermal vent fields was applied to investigate community diversity patterns among protistan assemblages. The four vent fields include Axial Seamount at the Juan de Fuca Ridge, Sea Cliff and Apollo at the Gorda Ridge, all in the NE Pacific Ocean, and Piccard and Von Damm at the Mid‐Cayman Rise in the Caribbean Sea. We describe species diversity patterns with respect to hydrothermal vent field and sample type, identify putative vent endemic microbial eukaryotes, and test how vent fluid geochemistry may influence microbial community diversity. At a semi‐global scale, microbial eukaryotic communities at deep‐sea vents were composed of similar proportions of dinoflagellates, ciliates, Rhizaria, and stramenopiles. Individual vent fields supported distinct and highly diverse assemblages of protists that included potentially endemic or novel vent‐associated strains. These findings represent a census of deep‐sea hydrothermal vent protistan communities. Protistan diversity, which is shaped by the hydrothermal vent environment at a local scale, ultimately influences the vent‐associated microbial food web and the broader deep‐sea carbon cycle.

Prevalence, trends, and individual patterns of long-term antidepressant medication use in the adult Swiss general population - Melanie A. Amrein; Michael P. Hengartner; Markus Näpflin; Renato Farcher; Carola A. Huber (European Journal of Clinical Pharmacology, 2023)
Purpose Antidepressant use has increased in many European countries, mostly driven by longer treatment duration. The aim of this study was to provide prevalence rates of long-term users of antidepressants for the Swiss population over the last decade and to investigate associated factors for longer use. Methods We examined the prevalence rates of individuals with at least one prescription for antidepressants using longitudinal health claims data for 2013 to 2021. We defined short- (< one year), medium- (one–two years), and long-term users (> two years) for 2015 to 2019. We applied a binary logistic regression model to investigate the effects of population (gender, age, area of living, language, health insurance plan, and nursing home) and treatment characteristics (psychiatric or psychotherapeutic care) on long-term compared to short- and medium-term users in 2019. Results In 2021, 9% of the Swiss population ( n = 770,698) received at least one antidepressant prescription, which remained stable since 2013. In 2019, the proportion of long-term users was 57.4%, with steady increase since 2015. The proportion of medium- and short-term users has decreased. Older age, being a woman, living in an urban area, living in a nursing home, being enrolled in a standard care plan, and receiving psychiatric or psychotherapeutic care were factors positively associated with being a long-term user. Conclusion The proportion of long-term users in Switzerland is high and steadily increasing. Given the ongoing debate about the confounding effects of relapse and withdrawal, more research is needed to investigate longer use of antidepressants that could indicate overprescribing.

Naïve Pine Terpene Response to the Mountain Pine Beetle (Dendroctonus ponderosae) through the Seasons - A. E. Musso; C. Fortier; D. P. W. Huber; A. L. Carroll; M. L. Evenden (Journal of Chemical Ecology, 2023)

Multiple parameters enable deconvolution of water-rock reaction paths in low-temperature vent fluids of the Kamaʻehuakanaloa (Lōʻihi) seamount - Vincent Milesi; Everett Shock; Jeffrey Seewald; Elizabeth Trembath-Reichert; Sean P. Sylva; Julie A. Huber; Darlene S.S. Lim; Christopher R. German (Geochimica et Cosmochimica Acta, 2023)

Controls on the presence and storage of soil inorganic carbon in a semi-arid watershed - Christopher Stanbery; Zahra Ghahremani; David P. Huber; Ryan Will; Shawn G. Benner; Nancy Glenn; Tanzila Hanif; Lucas Spaete; Danielle Terhaar; Kathleen A. Lohse; Mark Seyfried; William Freutel; et al. (CATENA, 2023)

Analytical chemistry solutions to hazard evaluation of petroleum refining products - Alina T. Roman-Hubers; Alexandra C. Cordova; Mark P. Barrow; Ivan Rusyn (Regulatory Toxicology and Pharmacology, 2023)

Accuracy, realism and general applicability of European forest models - Mats Mahnken; Maxime Cailleret; Alessio Collalti; Carlo Trotta; Corrado Biondo; Ettore D'Andrea; Daniela Dalmonech; Gina Marano; Annikki Mäkelä; Francesco Minunno; Mikko Peltoniemi; Volodymyr Trotsiuk; et al. (Global Change Biology, 2022)
Forest models are instrumental for understanding and projecting the impact of climate change on forests. A considerable number of forest models have been developed in the last decades. However, few systematic and comprehensive model comparisons have been performed in Europe that combine an evaluation of modelled carbon and water fluxes and forest structure. We evaluate 13 widely used, state‐of‐the‐art, stand‐scale forest models against field measurements of forest structure and eddy‐covariance data of carbon and water fluxes over multiple decades across an environmental gradient at nine typical European forest stands. We test the models' performance in three dimensions: accuracy of local predictions (agreement of modelled and observed annual data), realism of environmental responses (agreement of modelled and observed responses of daily gross primary productivity to temperature, radiation and vapour pressure deficit) and general applicability (proportion of European tree species covered). We find that multiple models are available that excel according to our three dimensions of model performance. For the accuracy of local predictions, variables related to forest structure have lower random and systematic errors than annual carbon and water flux variables. Moreover, the multi‐model ensemble mean provided overall more realistic daily productivity responses to environmental drivers across all sites than any single individual model. The general applicability of the models is high, as almost all models are currently able to cover Europe's common tree species. We show that forest models complement each other in their response to environmental drivers and that there are several cases in which individual models outperform the model ensemble. Our framework provides a first step to capturing essential differences between forest models that go beyond the most commonly used accuracy of predictions. Overall, this study provides a point of reference for future model work aimed at predicting climate impacts and supporting climate mitigation and adaptation measures in forests.

Removal of redox-sensitive Rubisco Activase does not alter Rubisco regulation in soybean - Christopher M. Harvey; Amanda P. Cavanagh; Sang Yeol Kim; David A. Wright; Ron G. Edquilang; Kayla S. Shreeves; Juan Alejandro Perdomo; Martin H. Spalding; Donald R. Ort; Carl J. Bernacchi; Steven C. Huber (Photosynthesis Research, 2022)

A wide range of protective and predisposing variants in aggrecan influence the susceptibility for otosclerosis - Allan Thomas Højland; Lisse J. M. Tavernier; Isabelle Schrauwen; Manou Sommen; Vedat Topsakal; Isabelle Schatteman; Ingeborg Dhooge; Alex Huber; Diego Zanetti; Henricus P. M. Kunst; Alexander Hoischen; Michael B. Petersen; et al. (Human Genetics, 2022)

Pathogenic STX3 variants affecting the retinal and intestinal transcripts cause an early-onset severe retinal dystrophy in microvillus inclusion disease subjects - Andreas R. Janecke; Xiaoqin Liu; Rüdiger Adam; Sumanth Punuru; Arne Viestenz; Valeria Strauß; Martin Laass; Elizabeth Sanchez; Roberto Adachi; Martha P. Schatz; Ujwala S. Saboo; Naveen Mittal; et al. (Human Genetics, 2021)
Biallelic STX3 variants were previously reported in five individuals with the severe congenital enteropathy, microvillus inclusion disease (MVID). Here, we provide a significant extension of the phenotypic spectrum caused by STX3 variants. We report ten individuals of diverse geographic origin with biallelic STX3 loss-of-function variants, identified through exome sequencing, single-nucleotide polymorphism array-based homozygosity mapping, and international collaboration. The evaluated individuals all presented with MVID. Eight individuals also displayed early-onset severe retinal dystrophy, i.e., syndromic—intestinal and retinal—disease. These individuals harbored STX3 variants that affected both the retinal and intestinal STX3 transcripts, whereas STX3 variants affected only the intestinal transcript in individuals with solitary MVID. That STX3 is essential for retinal photoreceptor survival was confirmed by the creation of a rod photoreceptor-specific STX3 knockout mouse model which revealed a time-dependent reduction in the number of rod photoreceptors, thinning of the outer nuclear layer, and the eventual loss of both rod and cone photoreceptors. Together, our results provide a link between STX3 loss-of-function variants and a human retinal dystrophy. Depending on the genomic site of a human loss-of-function STX3 variant, it can cause MVID, the novel intestinal-retinal syndrome reported here or, hypothetically, an isolated retinal dystrophy.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Local, Geographical, and Contextual Variation in the Aggregation Pheromone Blend of the Spruce Beetle, Dendroctonus rufipennis (Coleoptera: Curculionidae) - R. L. Isitt; K. P. Bleiker; D. S. Pureswaran; N. K. Hillier; D. P. W. Huber (Journal of Chemical Ecology, 2020)

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Diet in a bat assemblage in Atlantic Forest in southeastern Brazil - Ariana P. Gnocchi; Suéli Huber; Ana Carolina Srbek-Araujo (Tropical Ecology, 2019)

Rapid pre-eruptive thermal rejuvenation in a large silicic magma body: the case of the Masonic Park Tuff, Southern Rocky Mountain volcanic field, CO, USA - J. T. Sliwinski; O. Bachmann; M. A. Dungan; C. Huber; C. D. Deering; P. W. Lipman; L. H. J. Martin; C. Liebske (Contributions to Mineralogy and Petrology, 2017)

Study of Multi-phase Flow in Porous Media: Comparison of SPH Simulations with Micro-model Experiments - P. Kunz; I. M. Zarikos; N. K. Karadimitriou; M. Huber; U. Nieken; S. M. Hassanizadeh (Transport in Porous Media, 2016)
We present simulations and experiments of drainage processes in a micro-model. A direct numerical simulation is introduced which is capable of describing wetting phenomena on the pore scale. A numerical smoothed particle hydrodynamics model was developed and used to simulate the two-phase flow of immiscible fluids. The experiments were performed in a micro-model which allows the visualization of interface propagation in detail. We compare the experiments and simulations of a quasistatic drainage process and pure dynamic drainage processes. For both, simulation and experiment, the interfacial area and the pressure at the inflow and outflow are tracked. The capillary pressure during the dynamic drainage process was determined by image analysis.

Status of hormones and painkillers in wastewater effluents across several European states—considerations for the EU watch list concerning estradiols and diclofenac - P. Schröder; B. Helmreich; B. Škrbić; M. Carballa; M. Papa; C. Pastore; Z. Emre; A. Oehmen; A. Langenhoff; M. Molinos; J. Dvarioniene; C. Huber; et al. (Environmental Science and Pollution Research, 2016)

How do olivines record magmatic events? Insights from major and trace element zoning - C. Bouvet de Maisonneuve; F. Costa; C. Huber; P. Vonlanthen; O. Bachmann; M. A. Dungan (Contributions to Mineralogy and Petrology, 2016)

Pathogenesis of spring viremia of carp virus in emerald shiner Notropis atherinoides Rafinesque, fathead minnow Pimephales promelas Rafinesque and white sucker Catostomus commersonii (Lacepede) - E Misk; K Garver; E Nagy; S Isaac; L Tubbs; P Huber; L Al‐Hussinee; J S Lumsden (Journal of Fish Diseases, 2016)
Spring viremia of carp ( SVC ) is a reportable disease to the World Organization of Animal Health ( OIE ) as it is known to cause significant international economic impact. In Canada, the first and only isolation of SVC virus ( SVCV ) was in 2006, from common carp Cyprinus carpio L., at Hamilton Harbour, Lake Ontario. The susceptibility of fathead minnow Pimephales promelas Rafinesque, emerald shiner Notropis atherinoides Rafinesque and white sucker Catostomus commersonii (Lacepede) to intraperitoneal injection of the Canadian isolate ( HHO carp06) was evaluated using experimental infection, virus isolation, quantitative reverse transcription polymerase chain reaction ( qRT ‐ PCR ), histopathology and immunohistochemistry ( IHC ). Emerald shiner and fathead minnow were most susceptible with 43 and 53% cumulative mortality, respectively, compared with koi at 33%. Quantitative RT ‐ PCR demonstrated that koi had high viral loads throughout the experiment. At 34 days post‐infection, SVCV was detected from sampled emerald shiner and white sucker in very low titre and was not detected from fathead minnow. Koi, fathead minnow and emerald shiner had gross lesions typical of SVC disease. The histopathological picture was mostly dominated by necrotic changes in kidney, spleen, liver, pancreas and intestine. IHC further confirmed SVCV infection, and staining was largely correlated with histological lesions.

Dermocystidium‐like organism linked with a mortality event in yellow perch P erca flavescens ( M itchill) in O ntario, C anada - D Kirkbright; P Huber; B N Lillie; J S Lumsden (Journal of Fish Diseases, 2016)

Epitheliocystis in lake trout S alvelinus namaycush ( W albaum) is associated with a β‐proteobacteria - E Contador; P Methner; I Ryerse; P Huber; B N Lillie; S Frasca; J S Lumsden (Journal of Fish Diseases, 2016)
Lake trout Salvelinus namaycush (Walbaum) raised for stocking experienced yearly (2011–13) winter epizootics of epitheliocystis. Affected fish were dispersed on the bottom of the tank, had decreased feed and fright response, and mortality often reached 40%. Peak mortality occurred within 3 weeks of the appearance of clinical signs, and outbreaks typically lasted 6 weeks. Affected fish had no gross lesions but histologically had branchial epithelial necrosis and lamellar hyperplasia, with small to large numbers of scattered epithelial cells containing 10‐ to 20‐μm inclusions. A longitudinal study was undertaken of one annual outbreak, and lamellar hyperplasia was most closely associated with mortality. The number of inclusions was statistically greater ( P rDNA bacterial primers in conjunction with laser capture microdissection of inclusions demonstrated that a β‐proteobacteria was consistently associated with affected gills and is more likely the cause of the disease in lake trout.

Human impacts and aridity differentially alter soil N availability in drylands worldwide - Manuel Delgado‐Baquerizo; Fernando T. Maestre; Antonio Gallardo; David J. Eldridge; Santiago Soliveres; Matthew A. Bowker; Ana Prado‐Comesaña; Juan Gaitán; José L. Quero; Victoria Ochoa; Beatriz Gozalo; Miguel García‐Gómez; et al. (Global Ecology and Biogeography, 2016)
Aims Climate and human impacts are changing the nitrogen ( N ) inputs and losses in terrestrial ecosystems. However, it is largely unknown how these two major drivers of global change will simultaneously influence the N cycle in drylands, the largest terrestrial biome on the planet. We conducted a global observational study to evaluate how aridity and human impacts, together with biotic and abiotic factors, affect key soil variables of the N cycle. Location Two hundred and twenty‐four dryland sites from all continents except A ntarctica widely differing in their environmental conditions and human influence. Methods Using a standardized field survey, we measured aridity, human impacts (i.e. proxies of land uses and air pollution), key biophysical variables (i.e. soil pH and texture and total plant cover) and six important variables related to N cycling in soils: total N , organic N , ammonium, nitrate, dissolved organic:inorganic N and N mineralization rates. We used structural equation modelling to assess the direct and indirect effects of aridity, human impacts and key biophysical variables on the N cycle. Results Human impacts increased the concentration of total N , while aridity reduced it. The effects of aridity and human impacts on the N cycle were spatially disconnected, which may favour scarcity of N in the most arid areas and promote its accumulation in the least arid areas. Main conclusions We found that increasing aridity and anthropogenic pressure are spatially disconnected in drylands. This implies that while places with low aridity and high human impact accumulate N , most arid sites with the lowest human impacts lose N . Our analyses also provide evidence that both increasing aridity and human impacts may enhance the relative dominance of inorganic N in dryland soils, having a negative impact on key functions and services provided by these ecosystems.

Bryostatin-1 Restores Blood Brain Barrier Integrity following Blast-Induced Traumatic Brain Injury - Brandon P. Lucke-Wold; Aric F. Logsdon; Kelly E. Smith; Ryan C. Turner; Daniel L. Alkon; Zhenjun Tan; Zachary J. Naser; Chelsea M. Knotts; Jason D. Huber; Charles L. Rosen (Molecular Neurobiology, 2015)

Walleye S ander vitreus ( M itchill) are relatively resistant to experimental infection with VHSV IVb and extant walleye strains vary in susceptibility - J Grice; A Reid; A Peterson; K Blackburn; L Tubbs; S Lord; P Huber; R Horricks; B Dixon; N C Bols; J S Lumsden (Journal of Fish Diseases, 2015)
Compared to fathead minnow, walleye demonstrate low susceptibility to experimental infection with VHSV IVb, regardless of route of exposure or water temperature at time of infection. In triplicate and duplicate groups, walleye were intraperitoneally (i.p.) injected (10 2 –10 8 pfu/fish) or waterborne‐exposed (w; 1.4 × 10 7 pfu mL −1 ) with VHSV IVb. High cumulative mortality (64–100%) and severe gross lesions associated with VHSV IVb infection were evident only in fish i.p. injected with 10 8 pfu at 12 °C. These fish had multifocal necrosis of several tissues including the gill and heart. There was no difference in mortality between walleye infected (w or i.p.) at 12 °C (spring stocking) compared with a declining temperature profile from 18 to 12 °C (fall stocking). There were significant differences ( P qPCR ).

Mutations of the SLIT2–ROBO2 pathway genes SLIT2 and SRGAP1 confer risk for congenital anomalies of the kidney and urinary tract - Daw-Yang Hwang; Stefan Kohl; Xueping Fan; Asaf Vivante; Stefanie Chan; Gabriel C. Dworschak; Julian Schulz; Albertien M. van Eerde; Alina C. Hilger; Heon Yung Gee; Tracie Pennimpede; Bernhard G. Herrmann; et al. (Human Genetics, 2015)

Microbial pelagic metabolism and CDOM characterization in a phytoplankton-dominated versus a macrophyte-dominated shallow lake - A. Torremorell; G. Pérez; L. Lagomarsino; P. Huber; C. Queimaliños; J. Bustingorry; P. Fermani; M. E. Llames; F. Unrein (Hydrobiologia, 2015)

Amyloid associated with neoplasia in two captive tricolour sharkminnows Balantiocheilus melanopterus Bleeker - S Russell; L Tubbs; D J McLelland; V LePage; K M Young; P Huber; J S Lumsden (Journal of Fish Diseases, 2015)
Amyloid associated with pancreatic adenocarcinoma was discovered in two captive adult tricolour sharkminnows Balantiocheilus melanopterus Bleeker found dead in a freshwater display. Enlarged abdomens expanded by bloody ascitic fluid and grossly visible masses of abnormal tissue were present surrounding sections of the stomach and intestine. Histologically, the masses were composed of areas of well‐organized exocrine pancreatic acini interspersed with cords of poorly differentiated, spindle‐shaped cells that compressed and effaced normal parenchyma. These cells possessed small numbers of cytoplasmic zymogen granules; the exocrine nature of these cells was confirmed using transmission electron microscopy ( TEM ). Fibrovascular connective tissue of the hepatopancreas and mesenteries was expanded by lightly eosinophilic, hyaline, homogeneous acellular material. Similar material greatly expanded the tunica media of large blood vessels in the hepatopancreas. After staining with Congo red or thioflavin T, this material exhibited red–green dichroism under polarized light or bright green fluorescence under ultraviolet light (255 nm), respectively. The non‐branching fibrils, of indeterminate length, had an approximate diameter of 10–20 nm using TEM . Although exocrine pancreatic neoplasia is relatively common in fish, the presence of amyloid is not. To our current knowledge, the latter has not yet been described in association with a neoplastic lesion in fish.

Diseases of captive yellow seahorse Hippocampus kuda B leeker, pot‐bellied seahorse Hippocampus abdominalis L esson and weedy seadragon Phyllopteryx taeniolatus ( L acépède) - V LePage; J Young; C J Dutton; G Crawshaw; J A Paré; M Kummrow; D J McLelland; P Huber; K Young; S Russell; L Al‐Hussinee; J S Lumsden (Journal of Fish Diseases, 2015)
Seahorses, pipefish and seadragons are fish of the F amily S yngnathidae. From 1998 to 2010, 172 syngnathid cases from the T oronto Z oo were submitted for post‐mortem diagnostics and retrospectively examined. Among the submitted species were yellow seahorses Hippocampus kuda Bleeker ( n = 133), pot‐bellied seahorses Hippocampus abdominalis Lesson ( n = 35) and weedy seadragons Phyllopteryx taeniolatus ( L acépède; n = 4). The three most common causes of morbidity and mortality in this population were bacterial dermatitis, bilaterally symmetrical myopathy and mycobacteriosis, accounting for 24%, 17% and 15% of cases, respectively. Inflammatory processes were the most common diagnoses, present in 117 cases. Seven neoplasms were diagnosed, environmental aetiologies were identified in 46 cases, and two congenital defects were identified.

Decreased expression of HLA-DQ and HLA-DR on cells of the monocytic lineage in cystic fibrosis - Thomas P. Hofer; Marion Frankenberger; Irene Heimbeck; Dorothe Burggraf; Matthias Wjst; Adam K. A. Wright; Maria Kerscher; Susanne Nährig; Rudolf M. Huber; Rainald Fischer; Loems Ziegler- Heitbrock (Journal of Molecular Medicine, 2014)

Climate and soil attributes determine plant species turnover in global drylands - Werner Ulrich; Santiago Soliveres; Fernando T. Maestre; Nicholas J. Gotelli; José L. Quero; Manuel Delgado‐Baquerizo; Matthew A. Bowker; David J. Eldridge; Victoria Ochoa; Beatriz Gozalo; Enrique Valencia; Miguel Berdugo; et al. (Journal of Biogeography, 2014)
Aim Geographical, climatic and soil factors are major drivers of plant beta diversity, but their importance for dryland plant communities is poorly known. The aim of this study was to: (1) characterize patterns of beta diversity in global drylands; (2) detect common environmental drivers of beta diversity; and (3) test for thresholds in environmental conditions driving potential shifts in plant species composition. Location Global. Methods Beta diversity was quantified in 224 dryland plant communities from 22 geographical regions on all continents except Antarctica using four complementary measures: the percentage of singletons (species occurring at only one site); Whittaker's beta diversity, β(W); a directional beta diversity metric based on the correlation in species occurrences among spatially contiguous sites, β( R 2 ); and a multivariate abundance‐based metric, β( MV ). We used linear modelling to quantify the relationships between these metrics of beta diversity and geographical, climatic and soil variables. Results Soil fertility and variability in temperature and rainfall, and to a lesser extent latitude, were the most important environmental predictors of beta diversity. Metrics related to species identity [percentage of singletons and β(W)] were most sensitive to soil fertility, whereas those metrics related to environmental gradients and abundance [(β( R 2 ) and β( MV )] were more associated with climate variability. Interactions among soil variables, climatic factors and plant cover were not important determinants of beta diversity. Sites receiving less than 178 mm of annual rainfall differed sharply in species composition from more mesic sites (> 200 mm). Main conclusions Soil fertility and variability in temperature and rainfall are the most important environmental predictors of variation in plant beta diversity in global drylands. Our results suggest that those sites annually receiving c . 178 mm of rainfall will be especially sensitive to future climate changes. These findings may help to define appropriate conservation strategies for mitigating effects of climate change on dryland vegetation.

A rapid ex vivo tissue model for optimising drug detection and ionisation in MALDI imaging studies - K. Huber; M. Aichler; N. Sun; A. Buck; Z. Li; I. E. Fernandez; S. M. Hauck; H. Zitzelsberger; O. Eickelberg; K. P. Janssen; U. Keller; A. Walch (Histochemistry and Cell Biology, 2014)

In vitro antiproliferative effect of β-phenylethylamine derivatives and doxorubicin combinations on MCF/ADR cell lines - Wanda P. Almeida; Paula C. Huber; Luciana K. Kohn; João E. de Carvalho (Medicinal Chemistry Research, 2013)

Genetic Variation of Lodgepole Pine, Pinus contorta var. latifolia, Chemical and Physical Defenses that Affect Mountain Pine Beetle, Dendroctonus ponderosae, Attack and Tree Mortality - Daniel S. Ott; Alvin D. Yanchuk; Dezene P. W. Huber; Kimberly F. Wallin (Journal of Chemical Ecology, 2011)

Ecosystem, Location, and Climate Effects on Foliar Secondary Metabolites of Lodgepole Pine Populations from Central British Columbia - Christopher M. Wallis; Dezene P. W. Huber; Kathy J. Lewis (Journal of Chemical Ecology, 2011)

Phenotypic selection on floral scent: trade-off between attraction and deterrence? - Florian P. Schiestl; Franz K. Huber; José M. Gomez (Evolutionary Ecology, 2011)

Viral haemorrhagic septicaemia virus IVb inactivation by ultraviolet light, and storage viability at 4 and −20 °C - P Huber; B Petri; S Allen; J S Lumsden (Journal of Fish Diseases, 2010)

Viral haemorrhagic septicaemia virus IVb experimental infection of rainbow trout, Oncorhynchus mykiss (Walbaum), and fathead minnow, Pimphales promelas (Rafinesque) - L Al‐Hussinee; P Huber; S Russell; V LePage; A Reid; K M Young; E Nagy; R M W Stevenson; J S Lumsden (Journal of Fish Diseases, 2010)
Viral haemorrhagic septicaemia virus (VHSV) in the Great Lakes has had a dramatic impact on fish husbandry because of the implications of the presence of a reportable disease. Experimental infections with VHSV IVb were conducted in rainbow trout, Oncorhynchus mykiss (Walbaum), and fathead minnows, Pimphales promelas (Rafinesque), to examine their susceptibility and the clinical impact of infection. Triplicate groups of rainbow trout ( n = 40) were injected intraperitoneally (i.p.) with 100 μL 10 6.5 50% tissue culture infective doses (TCID 50 ) or waterborne exposed to graded doses (10 4.5 , 10 6.5 , and 10 8.5 TCID 50 mL −1 ) of VHSV IVb. Duplicate groups of fathead minnows ( n = 15) were i.p. injected with (10 6.5 TCID 50 100 μL) or waterborne exposed (10 6.5 TCID 50 mL −1 ). All experiments were performed with single‐pass well water maintained at 12 °C. Following either i.p. or waterborne exposure, VHSV RNA was detectable in both rainbow trout and fathead minnows by nested reverse transcription polymerase chain reaction (nRT‐PCR) as early as 4–7 days post‐infection (p.i.). Infected fathead minnow and rainbow trout exhibited lesions characteristic of VHS at 9 and 15 days p.i., respectively. Route of exposure had little effect on the onset of clinical signs. Cumulative mean mortality in rainbow trout was 4.4%, 2.6%, 2.6% and less than 1% in the i.p., high, medium and low dose waterborne exposures, respectively. Cumulative average mortality of 50% and 13% occurred in i.p. and waterborne‐exposed fathead minnows, respectively. VHSV was detected from pooled rainbow trout tissue by RT‐PCR and virus isolation at 38 days p.i., but not at 74 days p.i., regardless of the exposure route. Immunohistochemistry (IHC) with a rabbit antibody to VHSV IVb revealed the viral tissue tropisms following infection, with the identification of viral antigen in myocardium and necrotic branchial epithelium of both species and in gonadal tissue of fathead minnows. Rainbow trout, but not fathead minnows, are relatively refractory to experimental infection with VHSV IVb.

Effectiveness of a procalcitonin algorithm to guide antibiotic therapy in respiratory tract infections outside of study conditions: a post-study survey - P. Schuetz; M. Batschwaroff; F. Dusemund; W. Albrich; U. Bürgi; M. Maurer; M. Brutsche; A. R. Huber; B. Müller (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Plasma ladderlectin concentration following sterile inflammation and Aeromonas salmonicida subsp . salmonicida infection - K M Young; A Czyrny; S Russell; P Huber; J S Lumsden (Journal of Fish Diseases, 2009)
Plasma samples obtained from rainbow trout either experimentally infected with Aeromonas salmonicida or injected with either A. salmonicida lipopolysaccharide (LPS) or a commercial A. salmonicida vaccine (Lipogen) were analysed by enzyme immunoassay to evaluate changes in rainbow trout ladderlectin (RTLL) concentrations during the acute phase response (APR). Plasma RTLL concentrations in fish injected with A. salmonicida LPS, vaccine or live A. salmonicida varied over a 10 day period, but did not significantly increase. In contrast, fish experimentally infected with A. salmonicida exhibited a modest, but statistically significant ( P 0.05), decrease in RTLL concentration. These studies demonstrate that RTLL is not detectably induced during the trout APR to sterile inflammation or A. salmonicida infection, but plasma concentration of this protein may be reduced during bacterial infection.

Life cycle performance of aluminium applications: foreword - Rudolph P. Huber (The International Journal of Life Cycle Assessment, 2009)

An immune‐complex glomerulonephritis of Chinook salmon, Oncorhynchus tshawytscha (Walbaum) - J S Lumsden; S Russell; P Huber; B A Wybourne; V E Ostland; M Minamikawa; H W Ferguson (Journal of Fish Diseases, 2008)
Chinook salmon from New Zealand were shown to have a generalized membranous glomerulonephritis that was most severe in large fish. Marked thickening of the glomerular basement membrane was the most consistent lesion, with the presence of an electron‐dense deposit beneath the capillary endothelium. Severely affected glomeruli also had expansion of the mesangium and loss of capillaries, synechiae of the visceral and parietal epithelium and mild fibrosis of Bowman’s capsule. Chinook salmon from British Columbia, Canada with bacterial kidney disease caused by Renibacterium salmoninarum had similar histological lesions. They also had thickened glomerular basement membranes that were recognized by rabbit antiserum to rainbow trout immunoglobulin. This was true only when frozen sections of kidney were used and not formalin‐fixed tissue. An attempt to experimentally produce a glomerulopathy in rainbow trout by repeated immunization with killed R. salmoninarum was not successful. Case records from the Fish Pathology Laboratory at the University of Guelph over a 10‐year period revealed that a range of species were diagnosed with glomerulopathies similar to those seen in Chinook salmon. The majority of these cases were determined to have chronic inflammatory disease. This report has identified the presence of immunoglobulin within thickened basement membranes of Chinook salmon with glomerulonephritis and supports the existence of type III hypersensitivity in fish.

Shade induced changes in biomechanical petiole properties in the stoloniferous herb Trifolium repens - Heidrun Huber; Jan de Brouwer; Hannie de Caluwe; Jelmer Weijschedé; Niels P. R. Anten (Evolutionary Ecology, 2008)

Shade induced changes in biomechanical petiole properties in the stoloniferous herb Trifolium repens - Heidrun Huber; Jan de Brouwer; Hannie de Caluwe; Jelmer Wijschedé; Niels P. R. Anten (Evolutionary Ecology, 2008)

How consistent are trends in arrival (and departure) dates of migrant birds in the UK? - T. H. Sparks; K. Huber; R. L. Bland; H. Q. P. Crick; P. J. Croxton; J. Flood; R. G. Loxton; C. F. Mason; J. A. Newnham; P. Tryjanowski (Journal of Ornithology, 2007)

The effects of dietary phosphorus deficiency on surface pH and membrane composition of the mucosa epithelium in caprine jejunum - R. Busche; B. Schröder; K. Huber; H. P. Sallmann; G. Breves (Journal of Comparative Physiology B, 2006)

How well do the central England temperature and the England and Wales precipitation series represent the climate of the UK? - P. J. Croxton; K. Huber; N. Collinson; T. H. Sparks (International Journal of Climatology, 2006)

Plant development scores from fixed-date photographs: the influence of weather variables and recorder experience - T. H. Sparks; K. Huber; P. J. Croxton (International Journal of Biometeorology, 2006)

Pine monoterpenes and pine bark beetles: a marriage of convenience for defense and chemical communication - Steven J. Seybold; Dezene P. W. Huber; Jana C. Lee; Andrew D. Graves; Jörg Bohlmann (Phytochemistry Reviews, 2006)

Metropolitan-scale Transport and Dispersion from the New York World Trade Center Following September 11, 2001. Part I: An Evaluation of the CALMET Meteorological Model - Robert C. Gilliam; Peter P. Childs; Alan H. Huber; Sethu Raman (Pure and Applied Geophysics, 2005)

Incidence of novel and potentially archaeal nitrogenase genes in the deep Northeast Pacific Ocean - Mausmi P. Mehta; Julie A. Huber; John A. Baross (Environmental Microbiology, 2005)
Summary Archaea have been detected throughout the oceanic water column and are quantitatively important members of picoplankton in the deep ocean. Two common groups, group I Crenarchaeota and group II Euryarchaeota, are consistently detected in warm hydrothermal fluid and are assumed to have been drawn into the subseafloor, mixed with hydrothermal fluid and then expelled. However, because they remain resistant to cultivation, very little is known about their physiology. Here we show that cold deep‐seawater from the axial valley of Endeavour Segment on the Juan de Fuca Ridge contains not only groups I and II archaea as expected, but also unique potentially archaeal nitrogenase ( nifH ) genes, which are required for nitrogen fixation. These nifH genes are phylogenetically distinct and have dissimilar G+C content compared with those of hydrothermal vent archaea, suggesting that they belong to non‐thermophilic deep‐sea archaea. Furthermore, this sample did not contain mcrA genes, which are present in methanogens, the only known archaeal nitrogen fixers. These nifH genes were not detected in upper water column samples, or in a deep‐seawater sample 100 km away from the spreading axis of the Juan de Fuca Ridge. We propose that these unique nifH genes may be localized to archaea that circulate through the nitrogen‐poor subseafloor at the mid‐ocean ridge as part of their life cycle.

Aerial and aquatic feeding in the silver arawana, Osteoglossum bicirrhosum - Dayv Lowry; Alpa P. Wintzer; Michael P. Matott; Lisa B. Whitenack; Daniel R. Huber; Mason Dean; Philip J. Motta (Environmental Biology of Fishes, 2005)

Identifying target regions for vigilance improvement under hormone replacement therapy in postmenopausal syndrome patients by means of electroencephalographic tomography (LORETA) - B. Saletu; P. Anderer; G. M. Saletu-Zyhlarz; D. Gruber; M. Metka; J. Huber (Psychopharmacology, 2005)

Laser-Induced Chlorophyll Fluorescence Measurements for Detecting the Nitrogen Status of Wheat (Triticum aestivum L.) Canopies - J. Schchtl; G. Huber; F.-X. Maidl; E. Sticksel; J. Schulz; P. Haschberger (Precision Agriculture, 2005)

Floral scent emission and pollinator attraction in two species of Gymnadenia (Orchidaceae) - Franz K. Huber; Roman Kaiser; Willi Sauter; Florian P. Schiestl (Oecologia, 2005)

GENOMIC HARDWIRING AND PHENOTYPIC PLASTICITY OF TERPENOID-BASED DEFENSES IN CONIFERS - DEZENE P. W. HUBER; STEVEN RALPH; JRG BOHLMANN (Journal of Chemical Ecology, 2004)

The role of environment in shaping the genetic diversity of the subalpine mosquito, Aedes rusticus (Diptera, Culicidae) - J. P. David; K. Huber; A. B. Failloux; D. Rey; J. C. Meyran (Molecular Ecology, 2003)
The relative involvement of larval dietary tolerance to the leaf‐litter toxic polyphenols in shaping population genetic structure of the subalpine mosquito Aedes rusticus was examined. This was compared with other parameters such as geographical range, type of vegetation surrounding the breeding site, and occurrence of annual larvicidal treatments. Population genetic structure was analysed at 10 presumed neutral polymorphic isoenzyme loci. Toxicological comparisons involved standard bioassays performed on larvae fed on toxic decomposed leaf litter. Significant overall genetic differentiation was observed among the 22 studied populations and within the five defined geographical groups. Analysis of molecular variance revealed an absence of relation between genetic and environmental parameters, genetic variance being essentially found within populations. This suggested that the larval dietary tolerance to the toxic leaf litter and the other studied parameters poorly influence population genetic structure. The local adaptation of subalpine mosquito populations to the surrounding vegetation thus appears as a labile trait. Such a dynamic adaptation is also suggested by the correlation between geographical and toxicological distances and the correlation between dietary tolerance to the leaf‐litter toxic polyphenols and annual larvicidal treatments.

IGF-1 up-regulates K+ channels via PI3-kinase, PDK1 and SGK1 - N. Gamper; S. Fillon; S. Huber; Y. Feng; T. Kobayashi; P. Cohen; F. Lang (Pflügers Archiv - European Journal of Physiology, 2002)

Pivotal role of the interstitial cells of Cajal in the nitric oxide signaling pathway of rat small intestine - Salmhofer H.; Neuhuber W.; Ruth P.; Huber A.; Russwurm M.; Allescher H. (Cell and Tissue Research, 2001)

Angiosperm Bark Volatiles Disrupt Response of Douglas-Fir Beetle, Dendroctonus pseudotsugae, to Attractant-Baited Traps - Dezene P. W. Huber; John H. Borden (Journal of Chemical Ecology, 2001)

Two Pheromones of Coniferophagous Bark Beetles Found in the Bark of Nonhost Angiosperms - Dezene P. W. Huber; Regine Gries; John H. Borden; Harold D. Pierce (Journal of Chemical Ecology, 1999)

Effects of ethylbenzene, toluene, and xylene on the induction of micronuclei in bone marrow polychromatic erythrocytes of mice - E. Mohtashamipur; K. Norpoth; U. Woelke; P. Huber (Archives of Toxicology, 1985)